INFLUENCE OF MAGNETIC FIELD AND BIOCOMPONENT CONTENT ON CHANGES IN DIESEL FUELS PROPERTIES - Tsyhanenko, Vitalii; Trofimov, Ihor (Science-based technologies, 2025)
The modern fuel industry is facing a number of challenges, including the need to reduce the negative impact on the environment, increase fuel efficiency and ensure the durability of internal combustion engines. Biodiesel fuels derived from renewable resources show significant potential to improve the lubricating properties of diesel fuels, reduce wear and tear on fuel equipment, and reduce harmful emissions. At the same time, these fuels have certain limitations, such as low oxidation resistance and insufficient low-temperature properties, which require further improvement. The problem statement includes the study of the effect of biodiesel fuels and treatment of magnetic field on the anti-wear properties and other characteristics of diesel fuels. Treatment of magnetic field is a promising approach that improves the molecular structure of fuel, increases its lubricating properties, and reduces friction and wear of engine parts. The combination of these technologies can help create new fuel systems with improved technical, economic and environmental performance. The results of the study show that the use of biodiesel can reduce the wear of fuel system parts by 10-15% and reduce CO emissions by 12%, while the fuel treatment of magnetic field helps to reduce the friction coefficient by 15-18% and wear of engine components by 20-25%. The combination of biodiesel and treatment of magnetic field provides a synergistic effect, including a 30% reduction in wear on parts, an 18% reduction in NOₓ emissions, and a 10% reduction in fuel consumption. The study also confirmed the improvement in engine stability due to the creation of a protective lubricant film. The conclusions emphasize that the combined use of biofuels and treatment of magnetic field is a promising solution for increasing the durability of fuel systems and improving the environmental friendliness of the transportation sector. Further research should be aimed at optimizing the composition of biodiesel, improving treatment of magnetic field technologies, and evaluating their impact on different types of engines in real-world conditions.